Philosophical thought in education as an approach across disciplines in all natures of knowledge. - Hassan, Aminuddin; Zainal Abiddin, Norhasni; Sim, Kuan Yew (Canadian Center of Science and Education, 2013)
It is important to understand the concept of philosophical thought within all natures of knowledge well. This writing attempts to explore the perspective of the philosophy of education in Home Economics subjects. As with any other educational disciplines, the subject of Home Economics which is a part of the curriculum in Malaysia have a clear direction and strategy in realizing the nation's desire to produce balanced and highly skilled human resources. Home Economics is not a trashy subject to be underestimated because, ironically, it supports the philosophy and ideals towards the nation's ambition. Without philosophy, there is no path that can be used as a guide to strengthen the actions and direction of educational philosophy. Without that support, the struggle of technical and vocational education cannot provide an impact on the industry and accomplish the aspirations of the nation as a whole. From the perspective of philosophy, the arguments in explaining the importance of knowledge of Home Economics will also be discussed in this paper.